Flexural Behavior of Rolled Steel I Beam with Different Stiffener Position - G, Prabha.; R, Emilreyan (International Journal of Engineering and Technology, 2018)
Economy, ease and speed of construction are the main factors for using steel as a building material. In this paper conventional hot rolled steel I-beam sections are considered as the main flexural member of industrial buildings. The main goal is to increase the load carrying capacity of the beam with inverted w shape stiffener condition at centre. The initiative was to identify the maximum load behaviour and deflection of steel beams with stiffener in the web. The performance of such beams has been considered only for vertical loads. Hot rolled steel beam of ISMB 100 with stiffener were tested to failure experimentally. The beams were simply supported at the ends and subjected to a 2 equal concentrated load applied at one third of span from both ends.Â  The deflection at centre of beam and various failure patterns are studied. All the beams were analyzed by the finite element method by using general finite element analysis software ANSYS and the results were compared with those obtained experimentally. The finite element results for deformation and ultimate strength shows good agreement with the corresponding values observed in the experiments. At last, a comparative study was carried out using finite element method to examine that which type of beam gives best performance during loading. The numerical results indicate that the use of hot rolled I section with stiffener is an economical and advantageous choice.Â